Особливості варіабельності серцевого ритму в дівчат підліткового періодуз різним рівнемвегетативної регуляції - Коцан, Ігор; Качинська, Тетяна; Берлач, Світлана; Kotsan, Igor; Kachynska, Tetyna; Berlach, Svetlana (Східноєвропейський Національний університет імені Лесі Українки, 2015)
різним рівнемвегетативної регуляції Статтю присвячено вивченню особливостей стану серцево-судинноїсистеми в осібжіночої статі з різним рівнем вегетативної регуляції. В період пубертатуметодамистатистичного, спектрального та часового аналізу виявлено збільшення впливу симпатичного рівнярегуляції на роботу серця під час виконання розумових та фізичних завдань. Indices of heart rate variability are reliable and objective indicators of autonomic nervous systemtonus (of its sympathetic and parasympathetic divisions) which in its turn reflect the changes in psycho-emotional state of a person, development of stress or any kind of tension. The purpose of this paper is to study the features of heart rate variability indices in adolescent the girls with different levels of autonomic regulation during physical and mental stress. The research was conducted on 40 females, 13–14 years old, divided into groups: I – females of parasimpatic type (n = 20), II – females of sympatic type (n = 20). The cardiointervalogram was registered with the usage of computer cardiographic complex «KardioLab». The recording of HRV was conducted in experimental situations: background test, recording of HRV after physical exercises, recording of HRV during fulfillmentof the cognitive tasks. Results of the study in the sympatic and parasimpatic type showed that after the physical and cognitive testing, an increase of HRV. From the beginning to the end of puberty is an increase in the influence of the sympathetic level of regulation on the heart in females, nezavisemo the level of autonomic regulation.
Heart Rate Variability in Adolescent Girls with Different Levels of Autonomic Regulation.
Keywords: варіативність серцевого ритму; парасимпатичний рівень вегетативної регуляції; симпа- тичний рівень вегетативної регуляції; heart rate variability; the level of parasympatic vegetative regulation; the level of sympatic vegetative regulation